Matildas, Terezas, Ophélias e Camilas: protagonizando mulheres do século XX no ensino de História com histórias em quadrinhos - Silva, Rosiane Ferreira da (2022)
This research is based on the analysis of the silencing and underrepresentation of women in the textbook and also on the analysis of the students' previous knowledge, highlighting the performances and protagonisms of women during the 20th century in Brazil through the Comics that can be used as teaching-learning tools to be worked within the Teaching of History. The time frame defined was Brazil in the 20th century, due to the fact that the 9th year of elementary school II studies events that occur in that century until the present day. There was the application of two questionnaires, whose objective was to verify the perception of the students about women and their previous knowledge in general. There was also an analysis of the textbook used by Maria do Carmo and João Jacinto municipal schools in the city of Bayeux/PB in order to understand how women are represented. The textbook is Estudar História: from the origins of man to the digital age of the modern publishing house whose authors are Barreto and Braick (2018). For the purposes of discussion and understanding of the problems of this work, we establish dialogues with works organized by Mary Del Priori (2004), Carla Bassanezi and Joana Maria Pedro (2013), regarding the approach of the historical performances of women in the 20th century, in addition to by Koselleck (2006), Hartog (2013), Albuquerque (2019), among other authors that address History and History Teaching. For the discussion on historical learning and comics in the teaching of History, we will dialogue with Bittencourt (2008), Vygotsky (2001, 2010), Paulo Freire (2002) (2019), Rubem Alves (2000), among others. As a result of this work, four comics were created, each of them starring female characters, which are: Matilda, Tereza, Ophélia and Camila interconnected with national narratives and contexts addressed by the LDH analyzed in this research, in order to be used as paradidactic material to support the History textbook. The comics of this work were illustrated voluntarily by the designer Fabiano Gomes and the designers Jaqueline Souza and Marcelle Irineu.